2009
DOI: 10.1097/rli.0b013e3181afbb1e
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Fat Distribution in Whole Body MRI With Generally Used Anthropometric Data

Abstract: : We compared different body measures and body fat devices with the whole body fat distribution acquired by MRI. Generally, there were significant correlations of all modalities with body fat content (TAT) and mainly with SCAT. Correlations with VAT compartment were much weaker and an adequate estimation of VAT is, therefore, not possible. Only WHR revealed significant correlations with the fat in the body center, but only in women. If it is important to investigate especially the VAT which is responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 15 publications
9
63
0
3
Order By: Relevance
“…It shows that moderate to strong relationships of BMI and WC with absolute tissue masses and with muscle tissue mass proportions in elderly subjects exist. These results confirm the findings of previous validation work using CT and MRI on living subjects (Ferrannini et al, 2008;Kvist et al, 1988;Lee et al, 2000;Ludesher et al, 2009). However cautious clinical interpretation is warranted since important inter-individual differences in tissue proportions were found in subjects with similar BMI and/or WC values.…”
Section: Inter-individual and Sex Specific Differences In Body Compossupporting
confidence: 82%
See 1 more Smart Citation
“…It shows that moderate to strong relationships of BMI and WC with absolute tissue masses and with muscle tissue mass proportions in elderly subjects exist. These results confirm the findings of previous validation work using CT and MRI on living subjects (Ferrannini et al, 2008;Kvist et al, 1988;Lee et al, 2000;Ludesher et al, 2009). However cautious clinical interpretation is warranted since important inter-individual differences in tissue proportions were found in subjects with similar BMI and/or WC values.…”
Section: Inter-individual and Sex Specific Differences In Body Compossupporting
confidence: 82%
“…These reference standards are based on predictive equations that assume constancy and/or homogeneity of the compartments without taking into account the human biological variation of tissue composition (Clarys et al, , 2010bDeurenberg, 2003;Scafoglieri et al, 2009Scafoglieri et al, , 2010. Ideally, validation as markers of adiposity should be performed against multi-compartment models of BC as provided by three-dimensional imaging techniques such as CT and MRI or against direct measurements of AT such as total body carbon assessment and whole-body dissection Kvist et al, 1988;Ludesher et al, 2009). Even though CT and MRI are often cited as in vivo reference standards for the quantification of tissue-system level components, publications describing validation of these techniques with human cadavers remain scarce (Abate et al, 1994;Foster et al, 1984;Janssens et al, 1994;Mitsiopoulos et al, 1998;Rossner et al, 1990;.…”
Section: Controversial Use Of Body Mass Index In Longevitymentioning
confidence: 99%
“…Ludescher et al 207 reported that WC, WHR, and BMI were significantly correlated with total adipose tissue, VAT, and SAT; HC was correlated with SAT and total adipose tissue in men and also with VAT in women. Moreover, when Lee et al 208 assessed which measure (WC, abdominal fat mass by dual-energy X-ray absorptiometry [DEXA], or abdominal fat mass by CT) was most strongly associated with metabolic risk factors in Korean women, they concluded that all methods were of comparable utility.…”
Section: Imaging Methods: Ct and Mrimentioning
confidence: 99%
“…The 40K labeled water dilution technique and BIA assessment depend on total body water and/or electrolyte distribution, which have been shown to be affected by GHD and GHRT (13,14). This may lead to an overestimation of changes in FFM using these methods (7,15,16). DEXA scan does not offer the possibility to differentiate between subcutaneous and visceral FM, a distinction which may be of particular clinical importance in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data suggest that abdominal cross-sectional imaging (MRI or CT) is less reliable than whole abdomen scanning in determining visceral FM (16,17). Furthermore, whole-body MRI has been established for the separate assessment of the different body fat compartments (total, subcutaneous, and visceral FM) in different scientific settings, including insulin-resistant conditions (18).…”
Section: Introductionmentioning
confidence: 99%